Measurement of range of motions of L3-L4 healthy spine through offsetting reflective markers and in silico analysis of meshed model - Kosalishkwaran, G. (Springer Verlag, 2019)
Degenerative disc disease (DDD) is a common condition in elderly population that can be painful and can significantly affect individualâs quality of life. Diagnosis of DDD allows prompt corrective actions but it is challenging due to the absence of any symptoms at early stages. In studying disc degeneration, measurement of the range of motion (RoM) and loads acting on the spine are crucial factors. However, direct measurement of RoM involves increased instrumentation and risk. In this paper, an innovative method is proposed for calculating RoM, emphasizing repeatability and reliability by considering the posterior thickness of the spine. This is achieved by offsetting the position of markers in relation to the actual vertebral loci. Three geometrically identical finite element models of L3-L4 are developed from a CT scan with different types of elements, and thereafter, mesh element-related metrics are provided for the assessment of the quality of models. The model with the best mesh quality is used for further analysis, where RoM are within ranges as reported in literature and in vivo experiment results. Various kinds of stresses acting on individual components including facet joints are analysed for normal and abnormal loading conditions. The results showed that the stresses in abnormal load conditions for all components including cortical (76.67Â MPa), cancellous (69.18Â MPa), annulus (6.30Â MPa) and nucleus (0.343Â MPa) are significantly greater as compared to normal loads (49.96Â MPa, 44.2Â MPa, 4.28Â MPa and 0.23Â MPa respectively). However, stress levels for both conditions are within safe limits (167â215Â MPa for cortical, 46Â MPa for the annulus and 3Â MPa for facets). The results obtained could be used as a baseline motion and stresses of healthy subjects based on their respective lifestyles, which could benefit clinicians to suggest corrective actions for those affected by DDD. Â© 2019, International Federation for Medical and Biological Engineering.